The relationship of some factors affecting dynamic-static balance and proprioceptive sense in elite wrestlers - Recep Aydın; Gülfem Ersöz; Ali Özkan (Physical Education of Students, 2021)
Background and Study Aim. The aim of this study is to identify and correlate some factors that are thought to affect the dynamic-static balance and proprioceptive senses of elite level wrestlers.